Defining the features of structural and phase transformations in the recycling of anthropogenic metallurgical waste containing refractory elements - Volokh, V.; Poliakov, A.; Yamshinskij, M.; Lukianenko, I.; Andreev, A.; Tsymbal, B. M.; Pedchenko, G.; Chorna, T.; Bilko, T.; Dzyuba, A.; Цимбал, Б. М. (ПП «ТЕХНОЛОГІЧНИЙ ЦЕНТР», 2022)
This paper reports a study into the features of the phase composition and microstructure of a master alloy obtained by using the reduction melting of oxide man-made waste. That was necessary to define those technological indicators that provide for an increase in the degree of extraction of alloying elements during the recycling of anthropogenic raw materials and the subsequent use of the alloying material. It has been determined that the phase composition of the alloy at a Si:C ratio in the charge of 0.11 mainly consisted of a solid solution of elements in α-Fe, as well as carbides Fe3C and Fe3W3C. At the Si:C ratios in the charge of 0.28 and 0.52, along with a solid solution of the elements in α-Fe, Fe8Si2C, Fe5Si3, and FeSiC, FeSi2 manifested themselves, respectively. The microstructure of the alloy demonstrated a clear manifestation of several phases with different content of alloying elements. Changing a Si:C ratio in the charge from 0.11 to 0.28 and 0.52 led to an increase in the residual silicon content (wt %) in the studied areas, from 0.00–0.25 to 0.12–1.79 and 0.20–2.11, respectively. At the same time, the carbon content (wt %) in the examined areas varied from 0.25–2.12 to 0.24–2.52 and 0.45–2.68, respectively. The content of alloying elements in the investigated areas varied within (wt %): W – 0.00–43.06, Mo – 0.00–32.72, V – 0.19–20.72, Cr – 0.69–33.94, Co – 0.00–3.96. Analysis of the study’s results reveals that the most acceptable ratio of Si:C in the charge is 0.52. In this case, there is a certain content of residual silicon along with carbon in the form of carbosilicide and silicide compounds. Such indicators of the alloy provide sufficient reducing capacity of the alloy when used. The properties of the alloy make it possible, when smelting steels, to replace part of those standard ferroalloys that do not have strict carbon restrictions.
Keywords: dross of alloy steels; oxide anthropogenic waste; reduction melting; X-ray phase studies